The Influence of Macroeconomic Factors on Business Decision Making: Case Study of PT Kereta Api Indonesia (Persero) - Ajeng Suta Mayangsari; Astrid Ayu Nastiti; Arfi Sintya Nabilla; Rusdi Hidayat N; Indah Respati Kusumasari (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This article discusses the impact of macroeconomic factors on the decision-making process at PT Kereta Api Indonesia (Persero), one of the largest transportation companies in Indonesia. In the face of a constantly changing economy, the company must consider various important aspects, such as inflation, interest rates, exchange rates, government policies, and global economic conditions, as well as the mitigation measures taken by PT Kereta Api Indonesia (Persero). This research aims to analyze how these macroeconomic factors influence the strategies and operational decisions made by the company's management. Using a comprehensive methodological approach, the study gathers both quantitative and qualitative data to identify patterns and relationships between these factors and overall business performance. The findings indicate that changes in macroeconomic factors can significantly affect operational costs, investment planning, and the development of new services. These findings are expected to provide valuable insights for management in formulating more responsive and adaptive strategies to changes in economic conditions.